Seed Storage Physiology of Lophomyrtus and Neomyrtus, Two Threatened Myrtaceae Genera Endemic to New Zealand - Karin van der Walt; Jayanthi Nadarajan (Plants, 2023)
There is no published information on the seed germination or seed storage physiology of Lophomyrtus bullata, Lophomyrtus obcordata, and Neomyrtus pedunculata. This lack of information is hampering conservation efforts of these critically endangered species. This study investigated the seed morphology, seed germination requirements, and long-term seed storage methods for all three species. The impact of desiccation, desiccation and freezing, as well as desiccation plus storage at 5 °C, −18 °C, and −196 °C on seed viability (germination) and seedling vigour was assessed. Fatty acid profiles were compared between L. obcordata and L. bullata. Variability in storage behaviour between the three species was investigated through differential scanning calorimetry (DSC) by comparing thermal properties of lipids. L. obcordata seed were desiccation-tolerant and viability was retained when desiccated seed was stored for 24 months at 5 °C. L. bullata seed was both desiccation- and freezing-sensitive, while N. pedunculata was desiccation-sensitive. DSC analysis revealed that lipid crystallisation in L. bullata occurred between −18 °C and −49 °C and between −23 °C and −52 °C in L. obcordata and N. pedunculata. It is postulated that the metastable lipid phase, which coincides with the conventional seed banking temperature (i.e., storing seeds at −20 ± 4 °C and 15 ± 3% RH), could cause the seeds to age more rapidly through lipid peroxidation. Seeds of L. bullata, L. obcordata and N. pedunculata are best stored outside of their lipid metastable temperature ranges.